Herbaceous Undergrowth in some forest Habitats in Nilgiris - Rajvanshi, Rashmi; Kumar, Vijai; Bachpai, Waman; Rajagopal, K.; Francis Hilary Raj, S. (Indian Forester, 1987)
The herbaceous undergrowth under natural sholas was found qualitatively most rich and unique species composition. Eucalyptus planlatlon. Supported a good undergrowth both qualitatively and quantitatively, while pines have Much less undergrowth. A good grass cover Was found under Eucalyptus with a biomass of 998.6 ± 65.3 kg ha-1; tbe total biomass (kg ha-1) of herbs under the three forest covers were 445.8 ± 55.7 (Sbolas), 1135.1 ± 484 (Eucalyptus) and 54.7 ± 8.85 (plnes).